2002
DOI: 10.1006/enfo.2002.0086
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Applications of Nitrogen and Oxygen Isotopes in Tracing Nitrate Sources in Urban Environments

Abstract: Ground and surface waters in urban areas are susceptible to nitrate contamination from septic systems, leaking sewer lines, and fertilizer applications. Source identi®cation is a primary step toward a successful remediation plan in aected areas. In this respect, nitrogen and oxygen isotope ratios of nitrate, in conjunction with hydrologic data and water chemistry, have proven valuable in urban studies from Austin, Texas, and Tacoma, Washington.In Austin, stream water was sampled during strem¯ow and base¯ow con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
4
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 12 publications
(10 reference statements)
5
65
4
1
Order By: Relevance
“…Results from both studies implied that NO 3 in atmospheric deposition could contribute upwards of 50% of the NO 3 in these watersheds. Earlier studies by Ging et al (1996) and Silva et al (2002) using υ 18 O-NO 3 in two urbanized watersheds in Austin, Texas, also pointed to the importance of atmospheric NO 3 in stormflow due to the influence of runoff from impervious surfaces.…”
Section: General Trends In Nomentioning
confidence: 89%
See 1 more Smart Citation
“…Results from both studies implied that NO 3 in atmospheric deposition could contribute upwards of 50% of the NO 3 in these watersheds. Earlier studies by Ging et al (1996) and Silva et al (2002) using υ 18 O-NO 3 in two urbanized watersheds in Austin, Texas, also pointed to the importance of atmospheric NO 3 in stormflow due to the influence of runoff from impervious surfaces.…”
Section: General Trends In Nomentioning
confidence: 89%
“…For example, studies by Ging et al (1996) and Silva et al (2002) showed 3293 that υ 15 N-NO 3 was a useful tracer of NO 3 from sewage at baseflow, whereas increases in υ 18 O-NO 3 during storms were useful for inferring the importance of atmospheric NO 3 in direct runoff from impervious surfaces during stormflow in two heavily urbanized watersheds in Austin, Texas. More recent studies by Anisfeld et al (2007) and Burns et al (2009) have also suggested that υ 18 O-NO 3 may indicate important shifts to atmospheric NO 3 sources during high flows in urban and suburban watersheds.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, Cl − can be combined with δ 15 N-NO 3 − and δ 18 O-NO 3 − to identify NO − 3 sources and N transformation processes. Silva et al (2002) found that δ 15 N-NO 3 − values were positively related to Cl − concentrations in an urban watershed, indicating that the main NO − 3 source was mixing between baseflow and stormflow. Chen et al (2014) found that mixing processes played an important role in Taihu (Min et al 2002;Shin et al 2013) have found that water chemistry changed from a Ca-HCO 3 -to Na-Cl-NO 3 -dominated system when NO 3 − sources changed from soil organic N to sewage and manure.…”
Section: Combining Nitrogen and Oxygen Isotopes Of Nitrate With Chloridementioning
confidence: 95%
“…3 (Kendall 1998;Chang et al 2002;Silva et al 2002). NO 3 -originating from precipitation and synthetic NO 3 -fertilizer has much higher d 18 O values than that from nitrification of reduced N sources, i.e.…”
Section: Seasonal Variations Of Nitrate Sources and Dynamicsmentioning
confidence: 97%
“…This scenario is obviously unrealistic, because precipitation and river water were high in rainy August, which would dilute the contribution of sewage and livestock effluent. In fact, the most contribution of sewage and livestock effluent should be in dry December, Silva et al (2002). The shaded area defines the domain of nitrate from soil organic matter, which partially overlaps that of reduced N fertilizer and manure and sewage with respect to d 15 N. The two horizontal dashed lines delineate the local d 18 O of NO 3 -from these reduced N sources as described in the discussion.…”
Section: Seasonal Variations Of Nitrate Sources and Dynamicsmentioning
confidence: 98%